A multiwavelength study of the flat-spectrum radio quasar NVSS J141922−083830 covering four flaring episodes†. Issue 4 (1st August 2022) - Buckley, D A H; Britto, R J; Chandra, S; Krushinsky, V; Böttcher, M; Razzaque, S; Lipunov, V; Stalin, C S; Gorbovskoy, E; Tiurina, N; Vlasenko, D; Kniazev, A
ABSTRACT: We present multiwavelength observations and a model for flat-spectrum radio quasar (FSRQ) NVSS J141922−083830, originally classified as a blazar candidate of unknown type (BCU II object) in the Third Fermi - LAT AGN Catalog. Relatively bright flares (>3 magnitudes) were observed on 2015 February 21 (MJD 57074) and 2018 September 8 (MJD 58369) in the optical band with the MASTER Global Robotic Net telescopes. Optical spectra obtained with the Southern African Large Telescope on 2015 March 1 (MJD 57082), during outburst, and on 2017 May 30 (MJD 57903), during quiescence, showed emission lines at 5325 Å and at ≈3630 Å that we identified as the Mg ii 2798 Å and C iii ] 1909 Å lines, respectively, and hence derived a redshift z = 0.903. Analysis of Fermi - Large Area Telescope (LAT) data was performed in the quiescent regime (5 yr of data) and during four prominent flaring states in 2014 February–April, 2014 October–November, 2015 February–March, and 2018 September. We present spectral and timing analysis with Fermi - LAT . We report a hardening of the gamma-ray spectrum during the last three flaring periods, with a power-law spectral index Γ = 2.0–2.1. The maximum gamma-ray flux level was observed on 2014 October 24 (MJD 56954) at (7.57 ± 1.83) × 10 −7 ph cm −2 s −1 . The multiwavelength spectral energy distribution (SED) during the 2015 February–March flare supports the earlier evidence of this blazar to belong to the FSRQ class. The SED can be well represented with a single-zone leptonic model with parameters typical of FSRQs, but also a hadronic origin of the high-energy emission cannot be ruled out.